Parliamentary Activity from July to December 2024 (XIII Legislature) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2025)
The purpose of monitoring the parliamentary activity carried out in the Madrid Assembly, the subject of this parliamentary chronicle, is to provide information covering the months of July through December 2024, which includes the third session of the 13th Legislature.
Keywords: Parliamentary activity